Perspektif Kebijakan dan Praktik: Kesiapan Puskesmas di Indonesia terhadap Tanggap Darurat Kebakaran dalam Kajian Literatur - Fadilah, Sylva Qamara Nur; Hidayat, Ahmad Nur (RADINKA JAYA UTAMA PUBLISHER, 2024)
Community health centers, as providers of public health services at the local level, have a crucial role in saving lives and minimizing the impact of fires on health services. This study aims to assess the readiness of community health centers in Indonesia for emergency response to fires. This study uses a literature study approach. This article uses a narrative synthesis method and follows the PRISMA guidelines. Data were collected through a systematic search in ScienceDirect and Google Scholar with a limit of the last five years. The results of the literature study indicate that, when viewed in terms of human resources, most community health centers have formed a special team for emergency response to fires. In terms of budget, the funds used come from the allocation of community health center funds; for infrastructure, it is adequate with the presence of APAR, detectors, hydrants, and fire alarms. As for fire preparedness, it has followed the provisions of the Ministry of Health. This study concludes that overall, the readiness of community health centers in Indonesia for emergency response to fires is good, but several things need to be improved, especially in terms of human resources.